A closer look at Deep-fibre FTTdp - Watkins, Craig; Lillingstone-Hall, Kelvin (Journal of Telecommunications and the Digital Economy, 2020)
In this paper we outline a number of matters that have been raised in relation to Deep-fibre Fibre-to-the-Distribution-Point (FTTdp), and address practical ways that FTTdp can be expected to deliver a maximum overall cost-benefit outcome for the Australian NBN. We present brief discussions of some HFC (Hybrid Fibre Coax) and FTTN (Fibre-to-the-Node) issues considered of concern, to place FTTdp in perspective. We touch briefly on the threat from wireless communications to the fixed line technologies. We discuss the FTTdp equipment ecosystem, migration from legacy services to FTTN or FTTdp, in-building copper concerns, and LFN architecture savings emerging from the FTTdp approach. As previously, we conclude that FTTdp must be honestly evaluated if the nation is to achieve a maximal NBN capability outcome.